2014
DOI: 10.2217/pgs.14.48
|View full text |Cite
|
Sign up to set email alerts
|

Dose Reduction of Efavirenz: An Observational Study Describing Cost–Effectiveness, Pharmacokinetics and Pharmacogenetics

Abstract: The individualization of EFV dosage guided by genotyping 516G>T CYP2B6 and therapeutic drug monitoring could increase the efficiency of EFV use in antiretroviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…This suggests that central nervous system symptoms might decrease with lower doses. In one observational study in which doses were reduced in patients already receiving efavirenz, guided by CYP2B6 genotype and therapeutic drug monitoring, there were decreased central nervous system symptoms, continued virologic control and cost savings [20]. Economic considerations may increasingly affect ART prescribing, particularly with multiple options for initial ART with varying costs [1].…”
mentioning
confidence: 99%
“…This suggests that central nervous system symptoms might decrease with lower doses. In one observational study in which doses were reduced in patients already receiving efavirenz, guided by CYP2B6 genotype and therapeutic drug monitoring, there were decreased central nervous system symptoms, continued virologic control and cost savings [20]. Economic considerations may increasingly affect ART prescribing, particularly with multiple options for initial ART with varying costs [1].…”
mentioning
confidence: 99%
“…For example, one retrospective study reported that therapeutic dose monitoring and dose reduction in 31 patients with one or two 516 T alleles from a standard 600 mg/day dose of EFV to 400 mg/day, reduced the mean EFV C min (5.7 +/−3.4 mg/l at 600 mg/day) to within therapeutic range (2.39 +/− 1.28 mg/l at 400 mg/day) [47]. The authors also report that decreasing dosage in those patients also correlated with a decrease in the percentage of patients reporting CNS adverse events (from 89.3% to 9.7%), an increase in CD4 + lymphocyte counts (from 483.9-×10 6 cells/ μl to 600.8 × 10 6 cells/μl), and an increase in the percentage of patients with undetectable HIV viral load (from 93.5% to 100%.)…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…The authors also report that decreasing dosage in those patients also correlated with a decrease in the percentage of patients reporting CNS adverse events (from 89.3% to 9.7%), an increase in CD4 + lymphocyte counts (from 483.9-×10 6 cells/ μl to 600.8 × 10 6 cells/μl), and an increase in the percentage of patients with undetectable HIV viral load (from 93.5% to 100%.) Interestingly, all of the patients with the 516 T/T genotype required a further reduction to 200 mg/day EFV, supporting reduction in EFV dose for slow-metabolizers [47]. An important caveat before considering dose adjustment based on pharmacogenetic testing is that EFV and other anti-retrovirals are prescribed as part of a more complex regimen (ART and HAART) and may be administered as part of a fixed-dose co-formulation.…”
Section: Pharmacogeneticsmentioning
confidence: 99%
“…Efavirenz doses were substantially reduced down to 200 mg/d in these patients without loss of antiviral efficacy and improvement in CNS symptoms. In addition, CYP2B6 516G > T genotyping has been found to reduce treatment costs, even considering only the sparing related to efavirenz dose reduction [49] . These two reports constitute examples of practical applications of genotyping and how pharmacogenomics may be useful for the management of HIV-infected individuals receiving antiretroviral drugs.…”
Section: Nervous System Side Effectsmentioning
confidence: 99%